Family Planning Counseling Workers' Discretion in Contraception Policy Implementation: Analysis of the Role of Socio Demographic Characteristics of Acceptors in Demak District - Saidatun Ni’mah; Indra Kertati; Christian Charis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aims to analyze the discretion of family planning counselors in implementing contraceptive policies and the influence of acceptors' socio-demographic characteristics in Demak Regency. Using a mixed-methods approach with a sequential explanatory design, the study included 89 respondents for quantitative analysis and five key informants for in-depth interviews. The results showed a strong positive correlation between counselor discretion and acceptor socio-demographic characteristics (r = 0.646; p < 0.001), which explained 41.7% of the variance in discretionary practices. Counselors adapted communication strategies based on the age, education, geographic location, and culture of acceptors. Policy implementation faced obstacles in the counselor-community ratio (1:23) and the dominance of short-term contraceptive choices due to socio-cultural influences. Theoretical implications enrich the literature on street-level bureaucracy, while practical implications recommend strengthening counselors' capacity, increasing the ideal ratio, and implementing IEC strategies tailored to local culture. Limitations include a single geographic focus and a cross-sectional design. Future research is suggested to use longitudinal designs and multi-regional comparative studies to explore the dynamics of discretion in different socio-cultural contexts.